Building a master health facility list: innovative Indian experience. Issue 1 (22nd October 2020) - Mishra, Amit; Sahay, Sundeep
Abstract : Adoption of information technology in healthcare has in recent years improved the process of information collection, analysis and use in the Indian public health system. However, it has also led to multiplicity of information systems. Currently, a good amount of data is being generated by various health management information systems (HMISs); however, usability of these data sets is limited owing to lack of technical and institutional ability to share data with other systems. The lack of an effective standard list of health facilities is one of the major impediments to building interoperability among these multiple systems. To overcome this challenge, the Indian Ministry of Health and Family Welfare has initiated a programme to build a master facility list (MFL) known as National Identification Number to Health Facilities. Facility data from two leading national public health information systems, which were routinely reporting health data since 2008, were selected for this purpose. Common facilities were placed on an online portal for verification by state-level and district-level officers. Currently, this portal holds more than 200 000 verified public health facilities. Use of facility data from existing systems has helped to quickly populate the MFL in India. However, design limitations of the existing systems were also translated to the facility portal. Some lay challenges to sustain and evolve this portal in the future include (1) integration of other HMISs holding facility data with the MFL, (2) public notification of standards for MFL, (3) comprehensive data quality audit of existing MFL facility data and (4) establishment of robust governance mechanisms. We discuss how the benefits from this exercise in technical innovation can be materialised more effectively in practice.